Product liability for ADAS; legal and human factors perspectives - van Wees, Kiliaan; Brookhuis, Karel (European Journal of Transport and Infrastructure Research, 2005)
A variety of Advanced Driver Assistance Systems (ADAS) has been and is still being developed, aiming to make car driving more comfortable and safe, while at the same time enhancing traffic efficiency. However, the successful implementation of ADAS is affected by a variety of technical and non-technical issues, one of them being possible implications in the field of legal liability. Potential liability of system developers and car manufacturers is often labelled as a barrier for the rapid deployment of new technology. In the present contribution the European Product Liability Directive’s concept of a defective product is described and analysed from both a legal and a human factors perspective. In legal debates concerning product liability, generally two different approaches can be distinguished, one which is based on consumer expectations and a second which focuses, rather, on a risk-benefit analysis. As will be explained, the two may be seen as complementary and not as being mutually exclusive.Both tests can only be properly applied with the help of human factor expertise.